2003
DOI: 10.1177/0146167202238367
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Categorically Based Expectations on Minority Influence: The Importance of Congruence

Abstract: The role of congruence and incongruence in diverse decision-making groups is examined by manipulating opinion agreement within and between members of different social categories. Congruence occurs when ingroup members agree with one another and outgroup members disagree, whereas incongruence occurs when an ingroup member disagrees with a majority composed of ingroup and outgroup members. The results of two studies, one using a scenario methodology and the second using simulated work teams with two ingroup memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
162
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 48 publications
8
162
1
1
Order By: Relevance
“…For example, research on group diversity suggests that looking different from others in a group might increase a member's influence. When a person is different from other teammates, he or she is expected to have different knowledge or perspectives to add to the group, and, if that person speaks up, others are more receptive than they would be to a similar group member [27,28]. This biased attention to status and categorical cues that are unrelated to expertise and should be irrelevant can lead to undue influence for some members while leaving relevant knowledge of members with low status or from certain subgroups less likely to be considered and, therefore, less likely to influence the group's work.…”
Section: Expertise Usementioning
confidence: 99%
“…For example, research on group diversity suggests that looking different from others in a group might increase a member's influence. When a person is different from other teammates, he or she is expected to have different knowledge or perspectives to add to the group, and, if that person speaks up, others are more receptive than they would be to a similar group member [27,28]. This biased attention to status and categorical cues that are unrelated to expertise and should be irrelevant can lead to undue influence for some members while leaving relevant knowledge of members with low status or from certain subgroups less likely to be considered and, therefore, less likely to influence the group's work.…”
Section: Expertise Usementioning
confidence: 99%
“…This greater focus on being accepted and getting along (i.e., having social goals) with in-group members manifests itself in a number of ways. For instance, individuals prefer to work with (Jackson 1992), are more committed to (Doosje et al 2002), are more socially integrated with (O'Reilly et al 1989), want friendlier interactions with (Hornsey et al 2002;Moscovici 1980Moscovici , 1985, and expect more agreement from (Phillips 2003;Phillips and Loyd 2006) in-group than out-group members. Taken together, this suggests that individuals will be more relationship focused with in-group versus out-group members.…”
Section: The Relationship Between Social Category Diversity Relationmentioning
confidence: 99%
“…When you anticipate interacting with a group, if you know that even one person agrees with you, you may defer the responsibility of defending the position to the other party. Past research by Phillips and her colleagues examining the influence of congruence on group decision-making may be an appropriate framework and paradigm through which to test these ideas (e.g., Phillips 2003;Phillips et al 2009;Phillips and Loyd 2006;Phillips et al 2004). …”
Section: Relationship Focus Tradeoffmentioning
confidence: 99%
See 1 more Smart Citation
“…Rationale for CPerM notifications: Studies have shown that acknowledging the uniqueness of peripheral members' expertise may increase their confidence, and thus improve their level of participation and contribution (Phillips, 2003;Thomas-Hunt et al, 2003). In addition, CPerM can be motivated to participate more by becoming aware of the importance of their unique expertise for the rest of the community (Thomas-Hunt et al, 2003).…”
Section: Adaptive Notification Mechanismmentioning
confidence: 99%